Furanmonogones A and B: two rearranged acylphloroglucinols with a 4, 5-seco-3(2H)-furanone core from the flowers of Hypericum monogynum. Issue 2 (9th December 2016) - Xu, Wen-Jun; Luo, Jun; Li, Rui-Jun; Yang, Ming-Hua; Kong, Ling-Yi
Abstract : Rearranged acylphloroglucinols with an unprecedented 4, 5- seco -3(2 H )-furanone skeleton, furanmonogones A (1 ) and B (2 ), were isolated from the flowers of Hypericum monogynum . Abstract : Furanmonogones A (1 ) and B (2 ), two rearranged acylphloroglucinols with an unprecedented 4, 5- seco -3(2 H )-furanone skeleton, were isolated from the flowers of Hypericum monogynum . Their structures were established based on 1D- and 2D-NMR data, quantum chemical predictions (QCP) of 13 C NMR chemical shifts, and electronic circular dichroism (ECD) calculations. Baeyer–Villiger oxidation at the single bond (C4–C5) of the acylphloroglucinol core was proposed as a key step in the plausible biogenetic pathway of1 and2 .